2015
DOI: 10.1371/journal.pone.0120826
|View full text |Cite
|
Sign up to set email alerts
|

Viable Bacteria Associated with Red Blood Cells and Plasma in Freshly Drawn Blood Donations

Abstract: ObjectivesInfection remains a leading cause of post-transfusion mortality and morbidity. Bacterial contamination is, however, detected in less than 0.1% of blood units tested. The aim of the study was to identify viable bacteria in standard blood-pack units, with particular focus on bacteria from the oral cavity, and to determine the distribution of bacteria revealed in plasma and in the red blood cell (RBC)-fraction.DesignCross-sectional study. Blood were separated into plasma and RBC-suspensions, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 46 publications
6
109
2
5
Order By: Relevance
“…A recent study by Damgaard and colleagues (306) is of particular interest here. Recognizing the strong mismatch between the likelihood of an infection post-transfusion [very high (306)] and the likelihood of detecting culturable microbes in blood bank units (negligible, ca.…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study by Damgaard and colleagues (306) is of particular interest here. Recognizing the strong mismatch between the likelihood of an infection post-transfusion [very high (306)] and the likelihood of detecting culturable microbes in blood bank units (negligible, ca.…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 91%
“…Recognizing the strong mismatch between the likelihood of an infection post-transfusion [very high (306)] and the likelihood of detecting culturable microbes in blood bank units (negligible, ca. 0.1%) (306, 322), Damgaard et al reasoned that our methods of detecting and culturing these microbes might be the problem.…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 99%
“…The majority of brain abscesses are caused by blood-borne dissemination of periodontal organisms, often following an initiating dental intervention 17 22 23 92. Judicious dental hygiene is recommended to reduce post-toothbrushing93 and post-procedural94 bacteraemias and potential later reactivation of dormant bacteria 95. The use of prophylactic antibiotics prior to dental examinations and procedures is supported by a clinical trial indicating efficacy of intravenous and oral antibiotic regimes in limiting transient dental bacteraemias after tooth extractions94 and other guidance 96.…”
Section: Section 2: Medical Managementmentioning
confidence: 99%
“…Kalfin reported 100% positivity of the blood cultures. Subsequently several other authors questioned the existence of the blood microbiome or DNAemia in healthy individuals, Domingue (1977) [5], (1997) [7], Nikkari et al (2001) [8], Mc Laughlin et al (2002) [9], Moriyama et al (2008) [10], Markova (2015) [11], Damgaard (2015) [12] Dimova et al (2017) [13], Gosiewski et al (2017) [2] and Kowarsky et al (2017) [3]. The authors reported supporting electron microscopy, cultural and molecular data in favour of the existence of the blood microbiota in healthy individuals.…”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides Inmentioning
confidence: 99%
“…The authors reported supporting electron microscopy, cultural and molecular data in favour of the existence of the blood microbiota in healthy individuals. Hypothesis on the bacterial structure of the blood microbiota in healthy humans have been arisen [5] [6] [12], but cultures for exhaustive microbiota analysis remain a target. Rich bacterial diversity in the blood of healthy individuals was confirmed by 16S rRNA genes sequencing [14] and total RNA sequencing [15].…”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides Inmentioning
confidence: 99%